1994
DOI: 10.1542/peds.93.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Intervention Improves Maternal Psychological Well-being and Feeding Interaction of Preterm Infants

Abstract: Objective. To determine the efficacy of an individualized, family-based intervention with preterm infants and their families. Design. Randomized, repeated measures intervention outcome study. Setting. Level III neonatal intensive care nursery. Patients. Random sample of 34 preterm infants ≤1500 g and their families. Interventions. Individualized, family-based intervention during the hospitalization and transition to home addressed problems identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…This analysis revealed that both educational and active components seem to have their importance in parent-infant interventions with a predominance of a combination of the two components (Meyer et al, 1994;Newnham et al, 2009;Teti et al, 2009;White-Traut & Nelson, 1988;Zelkowitz et al, 2011), or an active component alone (Borghini et al, 2014;Browne & Talmi, 2005;Chiu & Anderson, 2009;Glazebrook et al, 2007;Hane et al, 2015;Hoffenkamp et al, 2015;Ravn et al, 2011;Sahlen Helmer et al, 2019;Twohig et al, 2019;White-Traut et al, 2013). The educational component usually encompasses different topics, and the active-participatory component relates to maternal participation in various caregiving activities of their preterm infant with direct guidance from a healthcare professional.…”
Section: Intervention Development Processmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis revealed that both educational and active components seem to have their importance in parent-infant interventions with a predominance of a combination of the two components (Meyer et al, 1994;Newnham et al, 2009;Teti et al, 2009;White-Traut & Nelson, 1988;Zelkowitz et al, 2011), or an active component alone (Borghini et al, 2014;Browne & Talmi, 2005;Chiu & Anderson, 2009;Glazebrook et al, 2007;Hane et al, 2015;Hoffenkamp et al, 2015;Ravn et al, 2011;Sahlen Helmer et al, 2019;Twohig et al, 2019;White-Traut et al, 2013). The educational component usually encompasses different topics, and the active-participatory component relates to maternal participation in various caregiving activities of their preterm infant with direct guidance from a healthcare professional.…”
Section: Intervention Development Processmentioning
confidence: 99%
“…Guidance is the most frequent mode of delivery of mother-infant interventions to enhance maternal sensitivity in previous studies (See Table 1, Appendix A; Borghini et al, 2014;Hoffenkamp et al, 2015;Meyer et al, 1994;Newnham et al, 2009;Ravn et al, 2011;Twohig et al, 2019;White-Traut et al, 2013). Guidance is based on the Guided Participation theory, specific on parenting, which has its origins from the Experiential Learning theory (Pridham et al, 1998).…”
Section: C) Guided Participation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Shaw, Connell, Dishion, Wilson, and Gardner (2009) found that engagement in the Family Check-Up (FCU), a preventive parent management skills intervention adapted for young children, was directly related to improvements in primary caregiver depression among families with 2- to 3-year-old children. Family interventions engaged in by parents of preterm infants have been shown to reduce maternal stress and depression over time (Meyer et al, 1994). A meta-analysis of the effectiveness of group-based parenting interventions applied during early childhood identified effects for parental depression and anxiety/stress, self-esteem, and partner relationship satisfaction (Barlow, Coren, & Stewart-Brown, 2002).…”
Section: Implications Of Parenting Interventions For Parent Well-beingmentioning
confidence: 99%
“…12 The most important things to prevent such a dreadful outcome are for physicians to identify infant colic effectively and to provide treatment goals for infant colic to support and counsel the caregivers on how to best respond to their infant's crying. 13,14 To our knowledge, Indonesian pediatricians' usage and understanding of Rome IV criteria with regards to infantile colic has never been reported. Therefore, this study was conducted to evaluate Indonesian pediatricians' understanding of infantile colic, with the hope that our results can serve as a basis to reduce the complexity of handling infantile colic and complement educational materials for students, specialist physician trainees, and pediatricians.…”
mentioning
confidence: 97%